Diagnosis challenges of often-overlooked infectious mononucleosis in Indonesia: to what extent do we need to explore common viral exanthems further - Bayak, Joshua E. R.; Christabelle, Marie; Wijanadi, Made C.; Wiwekanda, Agus B. W. (International Journal of Research in Medical Sciences, 2025)
Although the diagnosis of viral exanthema is relatively common, the specific cause of them is rarely identified due to their benign natural history. Infectious mononucleosis (IM), one of the most common causes of viral exanthema, is frequently overlooked in Indonesia due to its nonspecific symptoms that mimic other much more common diseases such as dengue fever and bacterial infections, with a more unpredictable outcome. This diagnostic challenge is particularly pronounced in children, where overlapping clinical features complicate identification and management. We present a case of a young female with IM, which have previously been epidemiologically diagnosed with another condition. Our case highlights the need for increased clinical awareness and tailored treatment approaches to address the unique needs of paediatric patients, especially in a setting of individuals with diverse cultural and ethnical backgrounds. Individualized care is essential to improve outcomes and prevent complications, emphasizing the importance of accurate diagnosis and appropriate management in resource-limited settings.